The role of cue utilisation in reducing the workload in a train control task. Issue 11 (2nd November 2017) - Brouwers, Sue; Wiggins, Mark W.; Griffin, Barbara; Helton, William S.; O'Hare, David
Abstract: Skilled performance has been characterised, in part, by the capacity to accurately identify and respond to patterns as cues in the environment. The outcome is a reduction in cognitive load and a greater residual capacity to undertake concurrent tasks. The present study was designed to examine the relationship between cue utilisation and temporal pattern recognition in the context of a simulated, rail control task. Sixty-one university students undertook an assessment of cue utilisation and engaged in a rail control simulation. The appearance and movement of trains followed a consistent but implicit (undisclosed) pattern. Throughout the second half of the rail task, a secondary task was included. The results indicated that participants with relatively higher cue utilisation were more likely to identify the implicit pattern of rail movements, were more accurate and responded more rapidly under increased workload conditions. The results suggest that a propensity to identify patterns as cues may provide an opportunity to reduce cognitive demands, thereby facilitating performance in a novel task. Implications for selection and system design are discussed. Practitioner Summary: This study was designed to explain differences in the way in which people learn, particularly when tasks involve recurring patterns. Using simulated rail control, the results indicated that participants who display behaviour that is indicative of the utilisation of cues also recognise patterns in the movement of simulated trains. This enables them to manage trains more effectively, even while undertaking other tasks.